2021
DOI: 10.1002/pol.20210454
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically strong and stiff supramolecular polymers enabled by fiber reinforced long‐chain alkane matrix

Abstract: Fiber-reinforced-concrete (FRC) mechanism refers short discrete fibers that are uniformly distributed and randomly oriented, which offers an effective way to improve the mechanical performance of concrete. In the design of supramolecular polymers, an analogous concept of FRC appears to have been considered very rarely-although fibrous structure has been frequently observed/generated during the supramolecular polymerization. In this work, we apply the alkane thermosets, octadecane (C 18 H 38 ) and tetracosane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Supramolecular polymers are formed through non-covalent, directional interactions between monomeric building blocks. Assembly of these polymers is reversible, which enables functions such as coating, self-healing, and responsiveness (Wei et al, 2014;Xiao et al, 2020b;Lv et al, 2021). Water is typically regarded as a solvent in the assembly of supramolecular polymers; however, in 2017, Qi and Dong et al reported a supramolecular polymer in which water acted as an indispensable comonomer in the supramolecular polymerization (Dong et al, 2017b).…”
Section: Ces With Structural Water: Water Act As An Essential Comonom...mentioning
confidence: 99%
“…Supramolecular polymers are formed through non-covalent, directional interactions between monomeric building blocks. Assembly of these polymers is reversible, which enables functions such as coating, self-healing, and responsiveness (Wei et al, 2014;Xiao et al, 2020b;Lv et al, 2021). Water is typically regarded as a solvent in the assembly of supramolecular polymers; however, in 2017, Qi and Dong et al reported a supramolecular polymer in which water acted as an indispensable comonomer in the supramolecular polymerization (Dong et al, 2017b).…”
Section: Ces With Structural Water: Water Act As An Essential Comonom...mentioning
confidence: 99%